The application of the lower view lock to improve posture and develop walking abilities in individuals with cerebral palsy - Kielevyainen L.M. ,; Volkova U.S. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to assess the impact of employing low-vision obstructions on the development of ambulation abilities and posture improvement in individuals with cerebral palsy. Methods and structure of the study. The research was conducted at the Center for Adaptive Physical Culture of Petrozavodsk State University over an eight-month period. The experimental group comprised ten individuals aged between 12 and 23, all of whom had been diagnosed with cerebral palsy. During the study, the participants engaged in adaptive physical education sessions, which involved a combination of traditional exercises in an upright position with movements and a more advanced approach — the lower field of peripheral vision was obscured using dribbling glasses, similar to those used in basketball. Results and conclusions. The evaluation of the outcomes at the conclusion of the trial revealed that the participants were able to decrease the time required to traverse a straight line of 5 meters by an average of 57%. Nine out of ten participants enhanced their accuracy in measuring distances, completely eliminating any spikes. The duration of maintaining balance in the Romberg test increased by more than twofold. The findings of the investigation can be applied in the development and improvement of walking for children with cerebral palsy.